2022
DOI: 10.1097/ta.0000000000003735
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury development in polytrauma and the safety of early repeated contrast studies: A retrospective cohort study

Abstract: BACKGROUND:The role of repeat intravenous contrast doses beyond initial contrast imaging in the development of acute kidney injury (AKI) for multiple injury patients admitted to the intensive care unit (ICU) is not fully understood. We hypothesized that additional contrast doses are potentially modifiable risk factors for worse outcomes. METHODS:An 8-year retrospective study of our institutional prospective postinjury multiple organ failure database was performed. Adult ICU admissions that survived >72 hours w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Despite this, the majority of the risk factors for AKI in trauma patients are non-modifiable, including injury severity and degree of physiological derangement [ 10 ]. Many of the modifiable risk factors in AKI are yet to be determined in high-quality prospective studies and with previously feared aspects of care such as intravenous contrast administration recently showing no association with AKI [ 35 ]. Therefore, in TR-associated AKI, clinicians have a unique opportunity to implement early treatment to reduce the burden and incidence of this morbid and lethal complication.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the majority of the risk factors for AKI in trauma patients are non-modifiable, including injury severity and degree of physiological derangement [ 10 ]. Many of the modifiable risk factors in AKI are yet to be determined in high-quality prospective studies and with previously feared aspects of care such as intravenous contrast administration recently showing no association with AKI [ 35 ]. Therefore, in TR-associated AKI, clinicians have a unique opportunity to implement early treatment to reduce the burden and incidence of this morbid and lethal complication.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that patients who received additional contrast within 72 h of their initial dose did not have increased odds of developing acute kidney injury. This is an important finding as the imaging studies and angiography far outweigh the risk of repeat contrast exposure within polytrauma patients [ 27 ]. Several recent large studies conclusively show no contrast nephropathy risk in most emergency imaging studies.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…Overall, 113 cohorts from 106 studies using 10 MOF definitions were included. Four scoring systems were used: Denver (three different cutoff values), 4,7,9,18–43 Goris (two different cutoff values), 5,44–53 Marshall (four different cutoff values), 9,19,54–83 and Sequential Organ Failure Assessment (SOFA) (two different cutoff values) 8,10,11,19,84–115 . See Table 1.…”
Section: Systematic Reviewmentioning
confidence: 99%